2009
DOI: 10.1093/jat/33.8.550
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Detection in Postmortem Samples Following Therapeutic Administration

Abstract: Cocaine is one of the most widely abused drugs and one that is frequently encountered in forensic toxicology laboratories. Most often, the detection of cocaine would lead toxicologists and forensic pathologists to believe that the drug was used illicitly; however, cocaine is an effective local anesthetic and vasoconstrictor and is used clinically in surgeries of the eye, ear, nose, and throat. Therefore, it is important to note that the presence of cocaine and its metabolites in forensic samples cannot always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It was later revealed that cocaine was used during his nasal surgery as a local anesthetic, which explained the presence of both cocaine and its metabolite (benzoylecgonine) in his urine specimen: it was from medical use of cocaine [12]. Three days later a surgical procedure was performed to repair his nose and he was released from the hospital later that day with a prescription of Percocet (oxycodone, 5 mg; and acetaminophen, 325 mg) for pain relief.…”
Section: Case Reportmentioning
confidence: 99%
“…It was later revealed that cocaine was used during his nasal surgery as a local anesthetic, which explained the presence of both cocaine and its metabolite (benzoylecgonine) in his urine specimen: it was from medical use of cocaine [12]. Three days later a surgical procedure was performed to repair his nose and he was released from the hospital later that day with a prescription of Percocet (oxycodone, 5 mg; and acetaminophen, 325 mg) for pain relief.…”
Section: Case Reportmentioning
confidence: 99%
“…In addition, family members may suffer from undue anguish if their loved one was falsely identifi ed as an illicit drug abuser (45) . Therefore, it is very important that not only medical review offi cers but also laboratory professionals including toxicologists and pathologists be aware of all sources of alternative explanations for positive GC/MS confi rmation of an abused drug in urine in a subject undergoing workplace drug testing.…”
Section: Discussionmentioning
confidence: 99%